Covenantal ethics as moral infrastructure: Discourse analysis of ʿAhd, trust, and social cohesion in Islam - alosaimi, Saud moqbel (Research Journal in Advanced Humanities, 2026)
Promise-keeping is routinely treated as a private virtue or a legal requirement, yet in many societies it also functions as moral infrastructure: the invisible system of expectations that makes social life predictable and cooperation rational. Building on an Arabic ethical-theological treatment of الوفاء بالعهد (al‑wafāʾ bi‑l‑ʿahd; “fulfilling covenants”) that surveys Qur’anic usage, Prophetic practice, and classical moral psychology, this article reframes ʿahd (covenant) as a multilevel concept that links inner virtue, interpersonal trust, and institutional legitimacy. Using a humanities methodology—semantic analysis of key moral terms (wafāʾ, ʿahd, mīthāq, ʿaqd, ghadr), close reading of representative Qur’anic passages, and comparative dialogue with social‑contract theory and virtue ethics—we argue for three theses. First, the Qur’an depicts covenants not merely as agreements but as accountable moral acts (“the covenant will be asked about”), thereby fusing legality with conscience and eschatological responsibility. Second, Prophetic covenantal practice demonstrates a politics of credibility: honoring agreements even under strategic pressure produces reputational capital, reduces cycles of retaliation, and stabilizes plural coexistence. Third, covenantal ethics can be modeled as an ecology spanning the micro (moral self‑binding), meso (family and community norms), and macro (state and international commitments) levels, providing a conceptual bridge between Islamic normative sources and contemporary concerns in advanced humanities—trust erosion, polarization, contractualism without virtue, and governance in plural societies. The article concludes with implications for public ethics, interfaith coexistence, digital commitments, and future interdisciplinary research on “covenantality” as a measurable dimension of social trust.